The Effect of Glyphosate on the Reproduction of Estuarine Crabs: Neohelice granulata as a Study Model - Rodríguez, Enrique M.; Medesani, Daniel A.; Canosa, Ivana S.; Avigliano, Luciana (Frontiers in Endocrinology, 2021)
This review summarizes the bulk of evidence about the effect of glyphosate, both pure and formulated, on the ovarian maturation of Neohelice granulata female crabs, as well as the effects of glyphosate on sperm production in males of the same species. After long-term in vivo assays, made during the 3-month pre-reproductive period of this species, both formulated and pure glyphosate were able to produce a significant incidence of oocyte reabsorption in the ovary, together with a concomitant decreased of vitellogenin content, at concentrations ranging from 0.2 to 1 mg/L. Despite this, after 32-day in vivo assays, glyphosate stimulated oocyte growth, in terms of a higher percentage of vitellogenic oocytes, suggesting that glyphosate could be acting as an endocrine disruptor. In vitro assays made with isolated ovarian pieces showed a decrease of vitellogenin content, in correlation with lower protein synthesis, although some advance in maturation was observed in the histological analysis. In male crabs exposed in vivo to both pure and formulated glyphosate at 1 mg/L, several reproductive imbalances were noted, such as a significant decrease of the sperm count, abnormal spermatophores, and possible disrupting effects of glyphosate on the androgenic gland.